Comparación de las técnicas de determinación de hemoglobina a partir del calculo del hematocrito y mediante una técnica espectròfotometrica de los estudiantes de segundo año de laboratorio clínico e histopatológico de la universidad nacional de chimborazo periodo 2008-2009 - Moyota Maigua, Martha Alexandra (2010)
The following research work is dedicated to verifying the results of the variation of hemoglobin of the same sample of healthy patients used two simple techniques. Blood samples were taken in test tubes with anticoagulant "EDTA" which allows us to maintain the state's own blood for later processing.